Aerogel composite material packaging structure and preparation method thereof

By grafting a hydrophobic modifier on the surface of the aerogel composite material and covering the plastic seal film to control the pore size, the problem of degradation of the thermal insulation performance of the aerogel composite material after packaging is solved, and its thermal insulation performance is significantly improved.

CN119704793APending Publication Date: 2025-03-28GONG YI VAN RES INNOVATION COMPOSITE MATERIAL CO LTD

Patent Information

Application Number
CN202311266665.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The thermal insulation performance of the packaged aerogel composite material is reduced.

Method used

By grafting a hydrophobic modifier on the surface of the aerogel composite and covering the encapsulation film made of plastic encapsulation material on the surface, the pore size of the aerogel composite is controlled to be between 5nm and 30nm.

Benefits of technology

The influence of the packaging film on the thermal insulation performance of aerogel composite materials is reduced, and the thermal insulation performance of the packaging aerogel composite materials is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119704793A_ABST
    Figure CN119704793A_ABST
Patent Text Reader

Abstract

The invention provides an aerogel composite material packaging structure and a preparation method thereof. The preparation method of the aerogel composite material packaging structure comprises the following steps: providing an aerogel composite material of which at least the surface is grafted with a hydrophobic modifier; the thickness of the aerogel composite material is 0.09 mm to 5 mm; coating the surface of the aerogel composite material with a packaging film; the thickness of the packaging film ranges from 0.01 mm to 0.3 mm, and the packaging film comprises a plastic packaging material. According to the preparation method of the aerogel composite material packaging structure, a modifier is grafted on the surface of an aerogel composite material, so that the permeation probability of liquid generated in the packaging film coating process and / or the permeation probability of liquid generated by heating and melting during thermal insulation application in a thermal environment after the packaging film is coated is reduced; therefore, the influence of the packaging film of the aerogel composite material on the heat insulation performance of the aerogel composite material is reduced, and the heat insulation performance of the packaged aerogel composite material packaging structure is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aerogel preparation, and in particular to an aerogel composite material packaging structure and a preparation method thereof. Background Art

[0002] Aerogel is known as a super thermal insulation material. It is usually compounded with inorganic fibers to make aerogel insulation felt, insulation boards or other special-shaped parts to give full play to the excellent thermal insulation properties of aerogel materials.

[0003] Aerogel is fragile. Aerogel composite materials are obtained by compounding aerogel with fiber felt. Aerogel composite materials still have the problem of powder falling when used in various fields such as batteries. Therefore, when aerogel composite materials are used in batteries, they need to be encapsulated and coated with a packaging film to avoid the influence of powder falling of aerogel composite materials on batteries.

[0004] However, the thermal insulation performance of the encapsulated aerogel composite material is reduced. Summary of the invention

[0005] The present application provides an aerogel composite packaging structure and a preparation method thereof, which mainly solve the technical problem of reduced thermal insulation performance of the encapsulated aerogel composite material.

[0006] In order to solve the above technical problems, a technical solution adopted in the present application is to provide a method for preparing an aerogel composite material packaging structure, comprising:

[0007] Providing an aerogel composite material having a hydrophobic modifier grafted at least on the surface; the aerogel composite material has a thickness of 0.09 mm to 5 mm;

[0008] A packaging film is coated on the surface of the aerogel composite material; the thickness of the packaging film is 0.01 mm-0.3 mm, and the packaging film includes a plastic packaging material.

[0009] In a specific embodiment, an aerogel composite material having the hydrophobic modifier grafted at least on the surface is provided, comprising:

[0010] The pore size of the aerogel pore structure of the aerogel composite material at least on the surface is controlled to be less than or equal to 30 nm.

[0011] In a specific embodiment, an aerogel composite material having the hydrophobic modifier grafted at least on the surface is provided, comprising:

[0012] The pore size of the pore structure of the aerogel composite material at least at the surface is controlled to be 5nm-30nm.

[0013] In a specific embodiment, the thickness of the aerogel composite material is 0.09 mm-2 mm.

[0014] In a specific embodiment, a packaging film is coated on the surface of the aerogel composite material, comprising:

[0015] The aerogel composite material is plastic-sealed by hot pressing; wherein the plastic-sealing material comprises one or more of a polyimide film, a polyester film, a polyurethane film, a polypropylene film, and a polyethylene film;

[0016] In a specific embodiment, the encapsulation film is attached to the upper and / or lower surface of the aerogel composite material by a resin adhesive;

[0017] Optionally, the resin adhesive includes epoxy resin.

[0018] In a specific embodiment, a packaging film is coated on the surface of the aerogel composite material, comprising:

[0019] A film-forming composition is coated on the surface of the aerogel composite material; wherein the film-forming composition comprises one or more of a water-based adhesive and a water-based coating.

[0020] In a specific embodiment, an aerogel composite material having the hydrophobic modifier grafted at least on the surface is provided, comprising:

[0021] combining the reinforcing substrate and the sol, gelling them, and drying them to obtain an aerogel composite material;

[0022] Using a hydrophobic modifier to modify at least the surface of the aerogel composite material, so that the hydrophobic modifier is grafted onto at least the surface of the aerogel composite material;

[0023] Or the aerogel composite material provided with a hydrophobic modifier grafted at least on the surface, comprising:

[0024] combining a sol including a hydrophobic modifier and a reinforcing substrate, gelling, and drying;

[0025] Or the aerogel composite material provided with a hydrophobic modifier grafted at least on the surface, comprising:

[0026] Combining the sol and the reinforcing substrate and gelling them to form a wet gel composite material, modifying the surface of the wet gel composite material with a hydrophobic modifier so that the hydrophobic modifier is grafted on at least the surface of the wet gel composite material; drying the wet gel composite material with the hydrophobic modifier grafted on at least the surface;

[0027] Or provide an aerogel composite material having the hydrophobic modifier grafted at least on the surface, comprising:

[0028] The sol including the hydrophobic modifier and the reinforcing substrate are combined, gelled, and dried to obtain a primary hydrophobically modified aerogel composite material; the surface of the primary hydrophobically modified aerogel composite material is subjected to secondary modification treatment using the hydrophobic modifier, so that the hydrophobic modifier is grafted onto at least the surface of the aerogel composite material;

[0029] Or provide an aerogel composite material having the hydrophobic modifier grafted at least on the surface, comprising:

[0030] The sol and the reinforcing substrate are combined and gelled to form a wet gel composite material, and a hydrophobic modifier is used to modify the surface of the wet gel composite material so that the hydrophobic modifier is grafted at least on the surface of the wet gel composite material; the wet gel composite material with the hydrophobic modifier grafted at least on the surface is dried to obtain an initially hydrophobically modified aerogel composite material; and the surface of the initially hydrophobically modified aerogel composite material is subjected to a secondary modification treatment using a hydrophobic modifier so that the hydrophobic modifier is grafted at least on the surface of the aerogel composite material;

[0031] Or provide an aerogel composite material having the hydrophobic modifier grafted at least on the surface, comprising:

[0032] A sol including a hydrophobic modifier and a reinforcing substrate are combined and gelled to obtain a primary hydrophobic modified wet gel composite material; a surface of the primary hydrophobic modified wet gel composite material is subjected to a secondary modification treatment using a hydrophobic modifier, and then dried to obtain an aerogel composite material at least on the surface of which the hydrophobic modifier is grafted.

[0033] In order to solve the above technical problems, another technical solution adopted in the present application is to provide an aerogel composite material packaging structure, comprising:

[0034] Aerogel composite material; the thickness of the aerogel composite material is 0.09 mm to 5 mm, and a hydrophobic modifier is grafted on at least the surface of the aerogel composite material;

[0035] The surface of the aerogel composite material is coated with the packaging film; the thickness of the packaging film is 0.01mm-0.3mm.

[0036] In a specific embodiment, the pore size of the pore structure of the aerogel composite material at least on the surface is less than or equal to 30 nm.

[0037] In a specific embodiment, the pore structure of the aerogel composite material at least at the surface has a pore size of 5 nm to 30 nm.

[0038] The present application provides an aerogel composite packaging structure and a preparation method thereof. The aerogel composite packaging structure includes providing an aerogel composite material having a hydrophobic modifier grafted at least on the surface; the thickness of the aerogel composite material is 0.09mm-5mm; a packaging film is coated on the surface of the aerogel composite material; the thickness of the packaging film is 0.01mm-0.3mm, and the packaging film includes a plastic packaging material. The preparation method of the aerogel composite packaging structure mainly reduces the probability of liquid infiltration during the coating of the packaging film and / or the probability of liquid infiltration caused by heat melting when the packaging film is applied for thermal insulation in a hot environment after the coating, thereby reducing the influence of the packaging film of the aerogel composite material on the thermal insulation performance of the aerogel composite material, so as to further improve the thermal insulation performance of the encapsulated aerogel composite material packaging structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0040] Figure 1 A flow chart of a method for preparing an aerogel composite packaging structure provided in one embodiment of the present application. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0042] In the following description, for the purpose of explanation rather than limitation, specific details such as specific system structures, interfaces, and technologies are provided to facilitate a thorough understanding of the present application.

[0043] The terms "first", "second", "third" in this application are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first", "second", "third" can expressly or implicitly include at least one of the features. In the description of this application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the embodiments of this application, all directional indications (such as up, down, left, right, front, back...) are only used to explain the relative position relationship, movement, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication also changes accordingly. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the steps or units listed, but optionally also includes steps or units that are not listed, or optionally also includes other steps or units inherent to these processes, methods, products or devices.

[0044] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0045] The inventors of the present application have found that, because the packaging film has better heat transfer performance than the product made of aerogel composite materials, when the aerogel composite materials are coated, the liquid generated by the packaging film during the hot pressing and plastic sealing process will flow and penetrate into the pore structure of the aerogel composite materials, and / or when the encapsulated aerogel composite material packaging structure is used for heat insulation in a hot environment, the packaging film is heated to generate liquid that will flow and penetrate into the pore structure of the aerogel composite materials, thereby affecting the thermal insulation performance of the aerogel composite materials, and further resulting in a reduction in the thermal insulation performance.

[0046] It should be noted that, in the process of coating the thick aerogel composite material with a packaging film, there will be liquid generated by the packaging film during the hot pressing and plastic sealing process that will penetrate into the pore structure of the aerogel composite material, and / or when the encapsulated aerogel composite material packaging structure is used for heat insulation in a hot environment, the liquid generated by the packaging film will flow and penetrate into the pore structure of the aerogel composite material. However, since the thickness of the thick aerogel composite material is much larger than the thickness of the packaging film, the amount of the packaging film flowing and penetrating into the pore structure of the aerogel composite material is smaller than the total amount of the pore structure of the aerogel composite material, and the packaging film has no obvious effect on the thermal insulation performance of the aerogel composite material. For ultra-thin aerogel composite materials, for example, aerogel composite materials with a thickness of less than 5 mm, the inventors found that packaging with a packaging film will cause a very significant decrease in thermal insulation performance, especially for aerogel composite materials with a thickness of less than 2 mm. The inventors found that packaging with a packaging film causes a more significant decrease in thermal insulation performance, which cannot meet product requirements.

[0047] The present application provides an aerogel composite packaging structure and a preparation method thereof. For ultra-thin aerogel composite materials, a hydrophobic modifier is grafted at least on the surface, which can reduce the infiltration of flowing liquids, thereby reducing the influence of the packaging film of the aerogel composite material on the thermal insulation performance of the aerogel composite material, so as to improve the thermal insulation performance of the aerogel composite material packaging structure after packaging. Furthermore, by controlling the aerogel composite material to have a smaller pore size, the infiltration of liquid generated by the packaging film during the packaging process and / or the infiltration of liquid generated by the packaging film when the aerogel composite material packaging structure after packaging is used for thermal insulation in a hot environment is further reduced, thereby further improving the thermal insulation performance of the aerogel composite material packaging structure after packaging.

[0048] The present application is described in detail below with reference to embodiments.

[0049] See also Figure 1 , Figure 1 A flow chart of a method for preparing an aerogel composite packaging structure provided in one embodiment of the present application.

[0050] The present application provides a method for preparing an aerogel composite packaging structure, comprising the following steps:

[0051] Step S1: providing an aerogel composite material having a hydrophobic modifier grafted at least on the surface.

[0052] Specifically, the thickness of the aerogel composite material is 0.09 mm-5 mm. For example, the thickness of the aerogel composite material can be 0.09 mm, 0.1 mm, 0.5 mm, 0.9 mm, 1.3 mm, 1.7 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm.

[0053] Step S2: coating the surface of the aerogel composite material with a packaging film.

[0054] The thickness of the packaging film is 0.01 mm-0.3 mm, and the packaging film includes a plastic packaging material. For example, the thickness of the packaging film can be 0.01 mm, 0.5 mm, 0.15 mm, 0.2 mm, 0.25 mm, or 0.3 mm.

[0055] The aerogel composite material has a pore structure at least on the surface. Since the packaging film is coated on the surface of the aerogel composite material in step S2, the liquid generated during the coating process penetrates into the pore structure of the aerogel composite material, and / or the packaging film is heated when the aerogel composite packaging structure after packaging is used for heat insulation in a hot environment. The liquid will flow and penetrate into the pore structure of the aerogel composite material, which will cause the thermal insulation performance of the aerogel composite material to decrease. This adverse effect of reducing the thermal insulation performance is more obvious in thin aerogel composite materials. In step S1, since a hydrophobic modifier is grafted at least on the surface of the aerogel composite material, it can reduce the liquid penetration generated by the packaging film during the packaging process, and / or the liquid penetration generated by the packaging film when the aerogel composite packaging structure after packaging is used for heat insulation in a hot environment, and the hydrophobic modifier itself can also adapt to high temperatures, therefore, the effect of the packaging film of the aerogel composite material on the thermal insulation performance can be reduced, so that the aerogel composite packaging structure obtained by the preparation method has excellent thermal insulation performance.

[0056] Furthermore, in a specific embodiment, step S1 may also include: controlling the pore size of the pore structure of the aerogel composite material at least at the surface to be less than or equal to 30 nm.

[0057] Controlling the aerogel composite material to have a smaller pore size can further reduce the penetration of liquid generated by the packaging film into the pore structure during the packaging process, and / or reduce the penetration of liquid generated by the packaging film into the pore structure when the encapsulated aerogel composite packaging structure is used for thermal insulation in a hot environment, thereby further reducing the impact of the packaging film of the aerogel composite material on the thermal insulation performance, so as to further improve the thermal insulation performance of the aerogel composite material packaging structure obtained using the preparation method.

[0058] Specifically, the pore size of the pore structure of the aerogel composite material at least at the surface is controlled to be less than or equal to 30 nm. The pore size is controlled by surface hydrophobic modification. The surface hydrophobic modification is mainly carried out by grafting some hydrophobic groups or side chains on the surface of the original pore structure to reduce the original pore structure to control the pore size to be less than or equal to 30 nm.

[0059] However, because the pore size of the pore structure is too small, there will be too little air in the aerogel composite material, which will increase the solid-state heat conduction and make the thermal insulation performance poor. In addition, the pore size of the pore structure is too small, which will increase the production cost of the aerogel. And because the pores can hinder the transfer of heat, the pore size is too small, which will lead to a decrease in thermal insulation performance. Therefore, in a specific embodiment, the pore size of the pore structure of the aerogel composite material at least at the surface is more preferably 5nm-30nm. For example, the pore size of the pore structure is 5nm, 10nm, 15nm, 20nm, 25nm, 30nm.

[0060] Specifically, the thickness of the aerogel composite material is 0.5mm-2mm. For aerogel composite materials with a thickness of less than 2mm, the inventors found that the thermal insulation performance is more significantly reduced when encapsulated with an encapsulation film. By grafting a modifier on the surface of the aerogel composite material to reduce the infiltration of liquid generated by heat melting during the encapsulation film coating process and after the encapsulation film is coated in a hot environment for thermal insulation applications, the effect of the encapsulation film of the aerogel composite material on the thermal insulation performance of the aerogel composite material is reduced, so as to further improve the thermal insulation performance of the encapsulated aerogel composite material packaging structure, and the effect of improving the thermal insulation performance of the aerogel composite material with a thickness of 0.5mm-2mm is more obvious.

[0061] At present, in the field of battery applications, the requirements for product thermal insulation performance are becoming increasingly higher. At the same time, as batteries become thinner and lighter, it is hoped that the thickness of the material used for thermal insulation is as thin as possible. Research has found that during the use of the battery, when the thickness of the existing aerogel composite material used for thermal insulation is less than 2 mm, the packaging film of the aerogel composite material in the thermal runaway heating environment of the battery will melt due to the heat and produce liquid infiltration, thereby causing the thermal insulation performance of the aerogel composite material to be significantly reduced, and it is unable to meet the battery's demand for thermal insulation performance and the normal use of the battery; and the thermal insulation performance of the aerogel composite material after the hydrophobic modifier is grafted on the surface of the aerogel composite material in the present application can be significantly improved.

[0062] In a specific embodiment, the encapsulation film is attached to the upper and / or lower surfaces of the aerogel composite material by a resin adhesive, and the resin adhesive is usually an epoxy resin adhesive. A modifier is grafted on the surface of the aerogel composite material to reduce the penetration of liquid generated by the resin adhesive being melted by heat during the encapsulation film coating process and after the encapsulation film coating in a hot environment.

[0063] In a specific embodiment, step S2 can also be performed in an environment higher than normal pressure. Because in a high-pressure environment, the gas also has a higher pressure, so that the gas pressure filled in the pore structure also increases. The increase in gas pressure can better prevent the liquid generated during the coating process from penetrating into the pore structure, thereby reducing the impact of the encapsulation film of the aerogel composite material on the thermal insulation performance, and further reducing the degradation of thermal insulation performance caused by encapsulation.

[0064] In a specific embodiment, the modification method mentioned in step S1 includes one of the following two methods, which is not limited in the present application.

[0065] Among them, the modification method 1 includes:

[0066] 1) combining the reinforcing substrate and the sol and gelling them to obtain an aerogel composite material;

[0067] 2) Using a hydrophobic modifier to modify at least the surface of the aerogel composite material, so that the hydrophobic modifier is grafted onto at least the surface of the aerogel composite material.

[0068] In a specific embodiment, the method uses a hydrophobic modifier to modify at least the surface of the gel obtained by combining and gelling the reinforcing substrate and the sol, and obtains an aerogel composite material after drying.

[0069] Specifically, the reinforcing substrate may be a fiber mat or a fiber cloth. The sol may be a silica sol, an alumina sol or a silica-alumina composite sol, which is not limited in the present application. Specifically, the present application embodiment mainly uses silica sol as an example for description.

[0070] The hydrophobic modifier can better reduce the penetration of liquid generated during the packaging process into the aerogel composite material, and / or reduce the penetration of liquid generated during the thermal insulation application of the packaging film into the aerogel composite material, and the hydrophobic modifier can adapt to the high-temperature use environment, and the hydrophobic modifier can maintain the hydrophobic effect without thermal decomposition when the packaging film and the resin binder are melted. The hydrophobic modifier contains at least two hydrophobic groups. The hydrophobic group is an alkyl group, and the alkyl chain group (CH) n , n≥2, the molecular formula of alkoxysilane is R 3m Si(OR4) (4-m) Wherein, R3 is a hydrophobic group, R4 is an alkyl group, m is the number of hydrophobic groups, 4-m is the number of alkyl groups, and the value of m is 2 or 3.

[0071] Specifically, the hydrophobic modifier includes any one or more of methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, chloropropyltriethoxysilane, chloropropyltrimethoxysilane, chloropropylmethyldimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, trimethylchlorosilane, hexamethyldisiloxane, and hexamethyldisilazane.

[0072] The hydrophobic modifier can be specifically used to modify the aerogel composite material in the form of a liquid phase or a gas phase, and this application does not limit this. Specifically, the hydrophobic modifier in gas phase is mainly obtained by heating and evaporating the hydrophobic modifier in liquid phase. In some embodiments, the aerogel composite material is modified by dipping the hydrophobic modifier in liquid or gas phase, or the aerogel composite material is modified by applying the hydrophobic modifier to the surface of the aerogel composite material by spraying or jetting. Among them, a catalyst is also added to the liquid phase modifier, and the catalyst can make the modification faster and the modification effect better. When used specifically, the catalyst is also diluted by adding a solvent. After the aerogel composite material is modified using the liquid phase modifier, the aerogel composite material is dried according to actual conditions.

[0073] Specifically, the catalyst is an inorganic base, an organic base or a mixture of an organic base and an inorganic base. The inorganic base includes any one or more of sodium hydroxide, potassium hydroxide, ammonia water, ammonium fluoride, ammonium bicarbonate, sodium carbonate and sodium bicarbonate; the organic base includes any one or more of ethanolamine, diethanolamine, methylamine, dimethylamine, ethylamine, diethylamine, propylamine, dipropylamine, isopropanolamine, aniline, o-phenylenediamine, m-phenylenediamine and p-phenylenediamine.

[0074] Specifically, the solvent is an alcohol solvent, which includes any one or more of methanol, ethanol, propanol, isopropanol, ethylene glycol, propylene glycol, and glycerol.

[0075] Among them, the modification method 2 includes:

[0076] The sol including the hydrophobic modifier and the reinforcing substrate are combined and gelled.

[0077] Specifically, the method is to add a hydrophobic modifier to a sol, then combine the sol including the hydrophobic modifier and a reinforcing substrate, gel, and dry to obtain an aerogel composite material having a hydrophobic modifier grafted on the surface. The specific hydrophobic modifier and the components and use methods of the reinforcing substrate are all described in method 1 and will not be repeated here. It can be understood that since the method introduces a hydrophobic modifier for modification during the sol process, it is easier to graft the hydrophobic modifier inside the micropores in the obtained aerogel composite material, and then the reinforcing substrate is mixed with the sol including the hydrophobic modifier to prepare the obtained aerogel composite material. The aerogel composite material has hydrophobic properties to further reduce the penetration of liquid generated by the encapsulation film into the interior of the gel composite material, and / or reduce the probability of liquid generated by the encapsulation film in the thermal insulation application process of the thermal environment into the interior of the aerogel composite material.

[0078] Among them, modification method three includes:

[0079] The sol and the reinforcing substrate are combined and gelled to form a wet gel composite material, so that the hydrophobic modifier is modified on the surface of the wet gel composite material, so that the hydrophobic modifier is grafted on at least the surface of the wet gel composite material; the wet gel composite material with the hydrophobic modifier grafted on at least the surface is dried.

[0080] The method introduces a hydrophobic modifier to modify the wet gel composite material before drying, which reduces the number of steps and reduces the production cost compared to introducing a liquid phase hydrophobic modifier on the surface of the aerogel composite material and then drying it; and compared to introducing a hydrophobic modifier into the sol, an aerogel composite material with a better surface hydrophobic effect can be obtained;

[0081] Among them, modification method 4 includes:

[0082] The sol including the hydrophobic modifier and the reinforcing substrate are combined, gelled and dried to obtain a primary hydrophobically modified aerogel composite material; the surface of the primary hydrophobically modified aerogel composite material is subjected to a secondary modification treatment using the hydrophobic modifier, so that the hydrophobic modifier is grafted on at least the surface of the aerogel composite material.

[0083] The method first modifies the sol by a hydrophobic modifier to prepare a sol including a hydrophobic modifier, and then mixes the reinforcing substrate with the sol including the hydrophobic modifier. Since the sol itself has fluidity, it can better enter the micropores, and at the same time drive the hydrophobic modifier into the micropores, so that the probability of grafting the hydrophobic modifier in the micropores is increased. The method can graft the hydrophobic modifier inside the micropores in the obtained aerogel composite material, and there is enough hydrophobic modifier grafted on the surface of the aerogel composite material, which has compensated for the problem of insufficient hydrophobic modifier grafted on the surface of the aerogel composite material caused by the hydrophobic modifier introduced into the sol and grafted inside the aerogel, so as to further reduce the penetration of liquid generated by the encapsulation film into the gel composite material during the encapsulation process, and / or reduce the penetration of liquid generated by the encapsulation film into the aerogel composite material during the thermal insulation application of the thermal environment. The method has a better and more significant effect on ultra-thin aerogel composite materials.

[0084] Among them, modification method five includes:

[0085] The sol and the reinforcing substrate are combined and gelled to form a wet gel composite material, and a hydrophobic modifier is used to modify the surface of the wet gel composite material so that the hydrophobic modifier is grafted at least on the surface of the wet gel composite material; the wet gel composite material with the hydrophobic modifier grafted at least on the surface is dried to obtain an initially hydrophobically modified aerogel composite material; and the surface of the initially hydrophobically modified aerogel composite material is secondarily modified by using a hydrophobic modifier so that the hydrophobic modifier is grafted at least on the surface of the aerogel composite material.

[0086] Since the hydrophobic modifier is combined with the sol, the gelation process of the sol is affected to a certain extent, resulting in incomplete formation of the skeleton produced by gelation, which affects the subsequent thermal insulation performance of the aerogel composite material; this method can make up for the problem of insufficient hydrophobic modifier grafted on the gel surface that may exist when the hydrophobic modifier is introduced before the wet gel composite material is dried, and further increase the hydrophobic modifier grafted on the surface of the aerogel composite material.

[0087] Among them, modification method six includes:

[0088] A sol including a hydrophobic modifier and a reinforcing substrate are combined and gelled to obtain a primary hydrophobic modified wet gel composite material; a surface of the primary hydrophobic modified wet gel composite material is subjected to a secondary modification treatment using a hydrophobic modifier, and then dried to obtain an aerogel composite material at least on the surface of which the hydrophobic modifier is grafted.

[0089] This method can make up for the problem of insufficient hydrophobic modifier grafted on the surface of the aerogel composite material caused by introducing a hydrophobic modifier into the sol and grafting the hydrophobic modifier inside the aerogel, so as to further increase the hydrophobic modifier grafted on the surface of the aerogel composite material.

[0090] In a specific embodiment, the coating packaging film mentioned in step S2 mainly includes any one of the following two methods, which is not limited in the present application.

[0091] Among them, packaging method one includes:

[0092] The aerogel composites were encapsulated by hot pressing.

[0093] Specifically, the plastic encapsulation material includes any one or more of polyimide film, polyester film, polyurethane film, polypropylene film, and polyethylene film. For example, the material of the plastic encapsulation film is a mixed material of the above-mentioned materials, or plastic encapsulation films of different materials can be set on the two opposite surfaces of the thermal insulation layer. The thermal conductivity of the aerogel composite material obtained after plastic encapsulation at room temperature is 0.014W / (m·K)-0.017W / (m·K). For example, the thermal conductivity of the aerogel composite material obtained after plastic encapsulation at room temperature can be 0.014W / (m·K), 0.015W / (m·K), 0.016W / (m·K), and 0.017W / (m·K).

[0094] When the plastic sealing material is a mixture of multiple films, multiple films are overlapped to prepare an overlapping film, and the multiple films are hot pressed to melt the films to prepare a composite film. The prepared composite film is wrapped in the prepared aerogel composite material and plastic sealed to obtain the composite film.

[0095] Among them, packaging method 2 includes:

[0096] A film-forming composition is coated on the surface of the aerogel composite material.

[0097] The film-forming composition is a fluid that can form an encapsulation film by drying. Specifically, the film-forming composition includes any one or more of an aqueous adhesive and an aqueous coating. For example, the aqueous adhesive and the aqueous coating are mixed to form an encapsulation film, or to form a laminated encapsulation film.

[0098] Specifically, the water-based adhesive includes any one of epoxy resin adhesive, acrylic adhesive, acrylate adhesive, EVA adhesive, polyester adhesive, polyether adhesive, polyurethane adhesive and polyurea adhesive.

[0099] Specifically, the water-based coating comprises a water-based elastic coating, a water-based resin, a flame retardant, a dispersant, a coupling agent, a silica powder and an aerogel powder in a mass ratio of (30-60): (10-40): (0-25): (1-5): (1-5): (0-5): (0-5). The water-based elastic coating comprises any one of a water-based ethylene-vinyl acetate elastic coating, a water-based silicone acrylic elastic coating, a water-based acrylic elastic coating and a water-based rubber latex, and the water-based resin comprises any one of a water-based epoxy resin, a water-based polyurea resin, a water-based phenolic resin and a water-based polyurethane resin.

[0100] Specifically, the thermal conductivity of the aerogel composite material coated with the film-forming composition at room temperature is 0.020W / (m·K)-0.030W / (m·K). For example, the thermal conductivity of the aerogel composite material coated with the film-forming composition at room temperature may be 0.020W / (m·K), 0.022W / (m·K), 0.024W / (m·K), 0.025W / (m·K), 0.026W / (m·K), 0.028W / (m·K), 0.030W / (m·K).

[0101] The present application also provides an aerogel composite packaging structure. The aerogel composite packaging structure includes an aerogel composite material and a packaging film. Among them, the thickness of the aerogel composite material is 0.09mm-5mm, and a hydrophobic modifier is grafted at least on the surface of the aerogel composite material. For example, the thickness of the aerogel composite material can be 0.09mm, 0.1mm, 0.5mm, 0.9mm, 1.3mm, 1.7mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm. In a specific embodiment, the hydrophobic modifier can better reduce the penetration of liquid generated during the packaging process into the interior of the aerogel composite material, and / or reduce the penetration of liquid generated during the thermal insulation application of the packaging film into the interior of the aerogel composite material, and the hydrophobic modifier can adapt to the high temperature use environment, therefore, the effect of the packaging film of the aerogel composite material on the thermal insulation performance can be reduced, so that the aerogel composite material packaging structure has excellent thermal insulation performance.

[0102] Specifically, the hydrophobic modifier includes any one or more of methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, chloropropyltriethoxysilane, chloropropyltrimethoxysilane, chloropropylmethyldimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, trimethylchlorosilane, hexamethyldisiloxane, and hexamethyldisilazane.

[0103] The packaging film is coated on the surface of the aerogel composite material; the thickness of the packaging film is 0.01-0.3 mm. For example, the thickness of the packaging film can be 0.01 mm, 0.5 mm, 0.15 mm, 0.2 mm, 0.25 mm, or 0.3 mm.

[0104] In a specific embodiment, the aerogel composite material has a pore structure at least on the surface. Preferably, the pore size of the pore structure of the aerogel composite material at least on the surface is less than or equal to 30 nm. The aerogel composite material has a smaller pore size, which can further reduce the penetration of liquid generated by the packaging film into the pore structure, and / or reduce the penetration of liquid generated by the melting of the packaging film in a thermal insulation application in a hot environment into the pore structure; thereby further reducing the effect of the packaging film of the aerogel composite material on the thermal insulation performance, so as to further improve the thermal insulation performance of the aerogel composite material packaging structure.

[0105] However, since too small a pore size of the pore structure will result in too little air in the aerogel composite material, resulting in poor thermal insulation performance, in a specific embodiment, the pore size of the pore structure of the aerogel composite material at least at the surface is more preferably 5nm-30nm. For example, the pore size of the pore structure is 5nm, 10nm, 15nm, 20nm, 25nm, 30nm.

[0106] The aerogel composite packaging structure provided in the present embodiment can reduce the liquid infiltration generated by the packaging film during the packaging process and / or reduce the liquid infiltration generated by the packaging film during the thermal insulation application of the packaging film in a thermal environment by grafting a hydrophobic modifier on at least the surface of the aerogel composite, thereby reducing the influence of the packaging film of the aerogel composite on the thermal insulation performance; and further reduce the influence of liquid infiltration on the thermal insulation performance of the aerogel composite by providing a pore structure with a smaller pore size on the surface of the aerogel composite, thereby further reducing the degradation of thermal insulation performance caused by packaging.

[0107] Hereinafter, the present invention will be described in more detail according to the following examples and comparative examples. However, the following examples and comparative examples are provided only to illustrate the present invention, and the scope of the present invention is not limited thereto.

[0108] Embodiment 1:

[0109] The silicon source precursor methyl orthosilicate and the hydrophobic modifier methyltrimethoxysilane, ethanol and water are stirred and mixed in a mass ratio of 1:2.5:40:1.5 to prepare a premixed solution, and 25% ammonia water is added to the premixed solution at a ratio of 0.09 mm, 0.5 mm, 1.0 mm, 1.5 mm and 2.0 mm to prepare a catalytic sol. The catalytic sol is applied to glass fiber felts with thicknesses of 0.09 mm, 0.5 mm, 1.0 mm, 1.5 mm and 2.0 mm, respectively. Before the catalytic sol is gelled, the catalytic sol is fully impregnated in the interior of the glass fiber felt. After the catalytic sol is fully impregnated in the glass fiber felt, it is gelled to obtain a wet gel felt. Subsequently, the gel felt is placed in a drying kettle, and the solvent and water in the wet gel felt are extracted through a supercritical drying process using carbon dioxide as a supercritical fluid to obtain a silica aerogel felt with a hydrophobic modifier grafted on the surface. The drying time is 12 hours. The silica aerogel felt grafted with a hydrophobic modifier on the surface is hot-pressed and packaged with a PET film of 0.05 mm thickness, and the surface of the silica aerogel felt grafted with a hydrophobic modifier is coated with a packaging PP film. The glass fiber felts are all prepared by a wet method, and the glass fiber felt can be used to prepare products with a thin thickness (≤2.0 mm) and uniform thickness. The aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 0.09 mm is recorded as sample 1-1, the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 0.5 mm is recorded as sample 1-2, the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 1.0 mm is recorded as sample 1-3, the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 1.5 mm is recorded as sample 1-4, and the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 2.0 mm is recorded as sample 1-5.

[0110] Embodiment 2:

[0111] The silicon source precursor methyl orthosilicate, ethanol and water were stirred and mixed in a mass ratio of 1:40:1.5 to prepare a premixed solution, and 25% ammonia water was added to the premixed solution at a mass ratio of 0.09 mm, 0.5 mm, 1.0 mm, 1.5 mm and 2.0 mm to prepare a catalytic sol. The catalytic sol was applied to glass fiber felts with thicknesses of 0.09 mm, 0.5 mm, 1.0 mm, 1.5 mm and 2.0 mm, respectively, and the catalytic sol was fully impregnated into the inside of the glass fiber felt before the catalytic sol was gelled. After the sol is fully impregnated with the glass fiber felt, it is gelled to obtain a wet gel felt. Ethanol, methyl trimethoxysiloxane, ammonium fluoride and water are mixed in a mass ratio of 100:20:0.1:5 to prepare a mixed hydrophobic modification liquid. The wet gel felt is placed in the mixed hydrophobic modification liquid and placed for 24 hours. The gel felt is then placed in a drying kettle. The solvent and water in the wet gel felt are extracted by a supercritical drying process using carbon dioxide as a supercritical fluid to obtain a silica aerogel felt. The drying time is 12 hours. The silica aerogel felt with a hydrophobic modifier grafted on the surface is hot-pressed and packaged with a PET film of 0.05 mm thickness, and the surface of the silica aerogel felt with a hydrophobic modifier grafted on the surface is coated with a packaging PP film. The glass fiber felts are all made by a wet method, and the glass fiber felt can be made into products with a thin thickness (≤2.0 mm) and uniform thickness by a wet method. The aerogel composite material packaging structure encapsulated by glass fiber aerogel felt with a thickness of 0.09 mm was recorded as Sample 2-1, the aerogel composite material packaging structure encapsulated by glass fiber aerogel felt with a thickness of 0.5 mm was recorded as Sample 2-2, the aerogel composite material packaging structure encapsulated by glass fiber aerogel felt with a thickness of 1.0 mm was recorded as Sample 2-3, the aerogel composite material packaging structure encapsulated by glass fiber aerogel felt with a thickness of 1.5 mm was recorded as Sample 2-4, and the aerogel composite material packaging structure encapsulated by glass fiber aerogel felt with a thickness of 2.0 mm was recorded as Sample 2-5.

[0112] Embodiment 3:

[0113] The difference from Example 2 is that the wet gel felt is no longer hydrophobically modified with a liquid phase hydrophobic modifier, and the aerogel felt after supercritical drying is subjected to gas phase hydrophobic modification to obtain a silica aerogel felt with a hydrophobic modifier grafted on the surface. The specific hydrophobic modification method is: placing the silica aerogel felt in a hydrophobic modification kettle, heating the liquid phase hydrophobic modifier methyltrimethoxysilane to the gas phase, and passing the gas phase methyltrimethoxysilane hydrophobic modifier into the hydrophobic modification kettle, and the gas phase hydrophobic modifier hydrophobically modifies the surface of the silica aerogel felt so that the hydrophobic modifier is grafted on the surface of the silica aerogel felt. The aerogel composite material packaging structure encapsulated by glass fiber aerogel felt with a thickness of 0.09 mm was recorded as Sample 3-1, the aerogel composite material packaging structure encapsulated by glass fiber aerogel felt with a thickness of 0.5 mm was recorded as Sample 3-2, the aerogel composite material packaging structure encapsulated by glass fiber aerogel felt with a thickness of 1.0 mm was recorded as Sample 3-3, the aerogel composite material packaging structure encapsulated by glass fiber aerogel felt with a thickness of 1.5 mm was recorded as Sample 3-4, and the aerogel composite material packaging structure encapsulated by glass fiber aerogel felt with a thickness of 2.0 mm was recorded as Sample 3-5.

[0114] Embodiment 4:

[0115] The difference from Example 2 is that the catalytic sol is applied to ceramic fiber felts with thicknesses of 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, and 5.0 mm, respectively. Ceramic fiber felt can be used in higher thermal environments than glass fiber felt. Generally, glass fiber felt is used in thermal environments below 650°C, and ceramic fiber felt is used in thermal environments below 1100°C. The aerogel composite material packaging structure after encapsulating a ceramic fiber aerogel felt with a thickness of 3.0 mm is recorded as sample 4-1, the aerogel composite material packaging structure after encapsulating a ceramic fiber aerogel felt with a thickness of 3.5 mm is recorded as sample 4-2, the aerogel composite material packaging structure after encapsulating a ceramic fiber aerogel felt with a thickness of 4.0 mm is recorded as sample 4-3, the aerogel composite material packaging structure after encapsulating a ceramic fiber aerogel felt with a thickness of 4.5 mm is recorded as sample 4-4, and the aerogel composite material packaging structure after encapsulating a ceramic fiber aerogel felt with a thickness of 5.0 mm is recorded as sample 5-5.

[0116] Embodiment 5:

[0117] The difference from Example 2 is that different amounts of ammonia water are added to the premixed solution to change the gelation speed of the catalytic sol and thereby reduce the pore size of the gel. Specifically, 25% ammonia water is added to the premixed solution at 15 / 10,000 of the total mass of the premixed solution, and the catalytic sol is obtained by stirring and mixing. The aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 0.09 mm is recorded as sample 5-1, the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 0.5 mm is recorded as sample 5-2, the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 1.0 mm is recorded as sample 5-3, the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 1.5 mm is recorded as sample 5-4, and the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 2.0 mm is recorded as sample 5-5.

[0118] Embodiment 6:

[0119] S1: Stir and mix the silicon source precursor methyl orthosilicate, ethanol and water in a mass ratio of 1:40:1.5 to prepare a premixed solution, add 25% ammonia water at a rate of 0.05% of the total mass of the premixed solution to the premixed solution, stir and mix to prepare a catalytic sol; apply the catalytic sol on glass fiber felts with thicknesses of 0.09 mm, 0.5 mm, 1.0 mm, 1.5 mm and 2.0 mm, respectively, fully impregnate the inside of the glass fiber felt with the catalytic sol before the catalytic sol gels, and gelate to obtain a wet gel felt after the catalytic sol fully impregnates the glass fiber felt;

[0120] Ethanol, methyltrimethoxysiloxane, ammonium fluoride and water were mixed in a mass ratio of 100:20:0.1:5 to prepare a mixed hydrophobic modification liquid, and a wet gel felt was placed in the mixed hydrophobic modification liquid for 24 hours to prepare a wet gel felt;

[0121] S2: The wet gel felt is then placed in a drying kettle, and the solvent and water in the wet gel felt are extracted through a supercritical drying process using carbon dioxide as a supercritical fluid to obtain a dry silica aerogel felt, and the drying time is 12 hours to prepare a dry aerogel felt; the dry aerogel felt is placed in a hydrophobic modification kettle body, and the liquid phase hydrophobic modifier methyltrimethoxysilane is heated to the gas phase, and the gas phase methyltrimethoxysilane hydrophobic modifier is introduced into the hydrophobic modification kettle body, and the gas phase hydrophobic modifier is used to hydrophobically modify the dry aerogel felt so that the hydrophobic modifier is grafted on the surface of the dry aerogel felt to obtain a composite aerogel composite material; the composite aerogel composite material is hot-pressed and packaged with a PET film with a thickness of 0.05 mm;

[0122] The glass fiber felts used in step S1 are all made by a wet method, and the glass fiber felts can be used to make products with a relatively thin thickness (≤2.0 mm) and uniform thickness. The aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 0.09 mm is recorded as sample 6-1, the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 0.5 mm is recorded as sample 6-2, the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 1.0 mm is recorded as sample 6-3, the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 1.5 mm is recorded as sample 6-4, and the aerogel composite material packaging structure after encapsulating the glass fiber aerogel felt with a thickness of 2.0 mm is recorded as sample 6-5.

[0123] Comparative Example 1:

[0124] The difference from Example 2 is that the wet gel felt is not subjected to hydrophobic modification, and the wet gel felt is directly subjected to supercritical drying to obtain a silica aerogel felt, and then the unhydrophobically modified silica aerogel felt is wrapped with a 0.05 mm thick PET film and hot-pressed. The aerogel composite material packaging structure after packaging a glass fiber aerogel felt with a thickness of 0.09 mm is recorded as Comparative Example 1-1, the aerogel composite material packaging structure after packaging a glass fiber aerogel felt with a thickness of 0.5 mm is recorded as Comparative Example 1-2, the aerogel composite material packaging structure after packaging a glass fiber aerogel felt with a thickness of 1.0 mm is recorded as Comparative Example 1-3, the aerogel composite material packaging structure after packaging a glass fiber aerogel felt with a thickness of 1.5 mm is recorded as Comparative Example 1-4, and the aerogel composite material packaging structure after packaging a glass fiber aerogel felt with a thickness of 2.0 mm is recorded as Comparative Example 1-5.

[0125] Comparative Example 2:

[0126] The pore size of the aerogel surface is relatively large, ranging from 50 to 100 nm. The proportion of silicon source precursors is different, the pore size is large, and no hydrophobic modification is performed.

[0127] The difference from Comparative Example 1 is that the silicon source precursor methyl orthosilicate, ethanol and water are stirred and mixed in a mass ratio of 1:60:1.5 to prepare a premixed solution, which is then impregnated with glass fiber felt, gelled and dried to obtain silica aerogel felt, and then the silica aerogel felt with a surface pore size of 50-100nm and not hydrophobically modified is wrapped with a 0.05mm thick PET film and hot-pressed. The aerogel composite material packaging structure after being packaged with a glass fiber aerogel felt with a thickness of 0.09 mm is recorded as Comparative Example 2-1, the aerogel composite material packaging structure after being packaged with a glass fiber aerogel felt with a thickness of 0.5 mm is recorded as Comparative Example 2-2, the aerogel composite material packaging structure after being packaged with a glass fiber aerogel felt with a thickness of 1.0 mm is recorded as Comparative Example 2-3, the aerogel composite material packaging structure after being packaged with a glass fiber aerogel felt with a thickness of 1.5 mm is recorded as Comparative Example 2-4, and the aerogel composite material packaging structure after being packaged with a glass fiber aerogel felt with a thickness of 2.0 mm is recorded as Comparative Example 2-5.

[0128] Table 1: Aerogel composite packaging structure performance test structure

[0129]

[0130]

[0131]

[0132]

[0133]

[0134] Through the experimental results of the above embodiments and comparative examples and Table 1, it can be clearly concluded that, compared with the aerogel composite material packaging structure obtained after the aerogel composite material packaging without hydrophobic modification treatment, the aerogel composite material packaging structure obtained after the aerogel composite material packaging after the surface hydrophobic modification treatment of the present application has significantly improved thermal insulation performance in a thermal environment of 500°C. In addition, the thermal insulation performance of the aerogel composite material packaging structure obtained after the aerogel composite material with a smaller pore size in the range of 5-20nm of the present application is also significantly improved compared with the thermal insulation performance of the aerogel composite material packaging structure obtained after the aerogel composite material with a smaller pore size in the range of 10-30nm is encapsulated.

[0135] It will be apparent to those skilled in the art that the present application is not limited to the details of the exemplary embodiments described above, and that the present application can be implemented in other specific forms without departing from the spirit or essential features of the present application. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the present application is defined by the appended claims rather than the above description, and it is intended that all changes within the meaning and scope of the equivalent elements of the claims be included in the present application. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0136] The above description is only an implementation method of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A method for preparing an aerogel composite packaging structure, characterized in that: include: Providing an aerogel composite material having a hydrophobic modifier grafted at least at the surface; The thickness of the aerogel composite material is 0.09 mm-5 mm; A packaging film is coated on the surface of the aerogel composite material; the thickness of the packaging film is 0.01 mm-0.3 mm, and the packaging film includes a plastic packaging material.

2. The method for preparing an aerogel composite material packaging structure according to claim 1, characterized in that: Provided is an aerogel composite material having the hydrophobic modifier grafted at least on the surface, comprising: The pore size of the aerogel pore structure of the aerogel composite material at least on the surface is controlled to be less than or equal to 30 nm.

3. The method for preparing an aerogel composite packaging structure according to claim 2, characterized in that: Provided is an aerogel composite material having the hydrophobic modifier grafted at least on the surface, comprising: The pore size of the pore structure of the aerogel composite material at least at the surface is controlled to be 5nm-30nm.

4. The method for preparing an aerogel composite packaging structure according to claim 1, characterized in that: The thickness of the aerogel composite material is 0.5 mm-2 mm.

5. The method for preparing an aerogel composite packaging structure according to claim 1, characterized in that: The surface of the aerogel composite material is coated with an encapsulation film, comprising: The aerogel composite material is plastic-sealed by hot pressing; wherein the plastic-sealing material comprises one or more of a polyimide film, a polyester film, a polyurethane film, a polypropylene film, and a polyethylene film; Optionally, the encapsulation film is attached to the upper and / or lower surface of the aerogel composite material by a resin adhesive; Optionally, the resin adhesive includes epoxy resin.

6. The method for preparing an aerogel composite packaging structure according to claim 1, characterized in that: The surface of the aerogel composite material is coated with an encapsulation film, comprising: A film-forming composition is coated on the surface of the aerogel composite material; wherein the film-forming composition comprises one or more of a water-based adhesive and a water-based coating.

7. The method for preparing an aerogel composite packaging structure according to claim 1, characterized in that: Provided is an aerogel composite material having the hydrophobic modifier grafted at least on the surface, comprising: combining the reinforcing substrate and the sol, gelling them, and drying them to obtain an aerogel composite material; Using a hydrophobic modifier to modify at least the surface of the aerogel composite material, so that the hydrophobic modifier is grafted onto at least the surface of the aerogel composite material; Or providing an aerogel composite material having the hydrophobic modifier grafted at least on the surface, comprising: combining a sol including a hydrophobic modifier and a reinforcing substrate, gelling, and drying; Or providing an aerogel composite material having the hydrophobic modifier grafted at least on the surface, comprising: Combining the sol and the reinforcing substrate and gelling them to form a wet gel composite material, modifying the surface of the wet gel composite material with a hydrophobic modifier so that the hydrophobic modifier is grafted on at least the surface of the wet gel composite material; drying the wet gel composite material with the hydrophobic modifier grafted on at least the surface; Or providing an aerogel composite material having the hydrophobic modifier grafted at least on the surface, comprising: The sol including the hydrophobic modifier and the reinforcing substrate are combined, gelled, and dried to obtain a primary hydrophobically modified aerogel composite material; the surface of the primary hydrophobically modified aerogel composite material is subjected to secondary modification treatment using the hydrophobic modifier, so that the hydrophobic modifier is grafted onto at least the surface of the aerogel composite material; Or providing an aerogel composite material having the hydrophobic modifier grafted at least on the surface, comprising: The sol and the reinforcing substrate are combined and gelled to form a wet gel composite material, and a hydrophobic modifier is used to modify the surface of the wet gel composite material so that the hydrophobic modifier is grafted at least on the surface of the wet gel composite material; the wet gel composite material with the hydrophobic modifier grafted at least on the surface is dried to obtain an initially hydrophobically modified aerogel composite material; and the surface of the initially hydrophobically modified aerogel composite material is subjected to a secondary modification treatment using a hydrophobic modifier so that the hydrophobic modifier is grafted at least on the surface of the aerogel composite material; Or providing an aerogel composite material having the hydrophobic modifier grafted at least on the surface, comprising: A sol including a hydrophobic modifier and a reinforcing substrate are combined and gelled to obtain a primary hydrophobic modified wet gel composite material; a surface of the primary hydrophobic modified wet gel composite material is subjected to a secondary modification treatment using a hydrophobic modifier, and then dried to obtain an aerogel composite material at least on the surface of which the hydrophobic modifier is grafted.

8. An aerogel composite packaging structure, characterized in that: include: Aerogel composites; The thickness of the aerogel composite material is 0.09 mm to 5 mm, and a hydrophobic modifier is grafted on at least the surface of the aerogel composite material; The surface of the aerogel composite material is coated with the packaging film; the thickness of the packaging film is 0.01nm-0.3mm.

9. The aerogel composite packaging structure according to claim 8, characterized in that: The pore size of the pore structure of the aerogel composite material at least on the surface is less than or equal to 30 nm.

10. The aerogel composite packaging structure according to claim 9, characterized in that: The pore size of the pore structure of the aerogel composite material at least on the surface is 5nm-30nm.

Citation Information

Patent Citations

  • Hydrophobic silicon dioxide aerogel felt and preparation method thereof

    CN114401925A

  • Low-dust aerogel product and preparation method thereof

    CN114801395A

  • Aerogel and heat insulator using aerogel

    JP2012172378A

  • Heat insulation material

    JP2015113924A

  • Heat insulation structure and manufacturing method of the same

    JP2018141525A

Cited By

  • Preparation process of low-temperature hot-pressing aerogel packaging film

    CN121733821A